A comparison between face-to-face and ODL implementations in increasing computer hands-on skills and social competence among UiTM Campus Seremban students / Sri Yusmawati Mohd Yunus ... [et al.] - Mohd Yunus, Sri Yusmawati; Noradzan, Haslinda; Wan Ghani, Wan Aryati; Mohd Isnani, Zaidatulhusna (2021)
Technology has been accepted as a platform for online teaching and learning among students all over the world. In Malaysia, most higher education institutions including Universiti Teknologi MARA (UiTM) have implemented online learning for students. UiTM introduced blended learning as a complementary approach to teaching and learning a few years ago. According to Bali and Liu (2018), a blended learning model or a blend of online classes has been around, however, the traditional approach is preferred and its effects on students' and instructors' experiences are yet to be fully explored.